Finite-Time Sliding Mode Control for Trajectory Tracking of WMRs with Wheel-Soil Friction Disturbance Adaptability. Issue 1 (2nd January 2017) - Yue, Ming; Gao, Junjie; Ma, Teng; Chen, Jun
ABSTRACT: This paper presents a trajectory tracking approach based on terminal sliding mode control (TSMC) technique for wheeled mobile robot where the wheel-soil friction can be measured and the estimated errors will converge to their stable values within finite-time, by which the control system is able to be designed in accordance with the prescribed performance. Three kinds of friction effects and their acting mechanisms, at the first place, are argued by exploring the disturbance-like friction behaviors, and then two updated laws, i.e., taking uncertain friction as an entire term or as a parametric form for varied effects, are proposed. In addition, the adoption of TSMC enables the tracking error estimation being faster and more reliable, and the stability and reliability of closed-loop control system are guaranteed by means of Lyapunov stability theorem. Subsequently, the numerical simulation validates the feasibility and effectiveness of the proposed controllers by which the terrain adaptability, movement precision, and maneuvering capability will be improved significantly.